Relationship between Consumption of Iron Supplements and Malaria Infection with Anaemia among Pregnant Mothers in Ambon City - Widy Markosia Wabula; Nyoman Tigeh Suryadhi; Luh Seri Ani (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: Maluku Province is one of the regions in Indonesia with the highest prevalence of anaemia among pregnant mothers; in addition, the prevalence of malaria in pregnant women in this province is also high. The aims of this study were to determine the relationship between consumption of iron supplements and malaria infection with anaemia of pregnant mothers in Ambon City Methods: This study used a cross-sectional design. Study sample was pregnant mothers in their 3rd trimester, and a total sample of 83 respondents was selected using multistage random sampling. Primary data on iron supplement intake were collected through interviews. Secondary data on malaria infection were obtained from medical records. Data on anaemia was obtained through collected blood samples using a digital hemometer. Data were analyzed using univariate, bivariate (chi-square test) and multivariate (logistic regression) analysis. Results: Multivariate analysis indicated there was a significant relationship between anaemia with consumption of iron supplement with OR=4.570 (95%CI: 1.174-17.788), as well as malaria infection with OR=20.216 (95%CI: 4.773-85.620). Conclusion: Malaria infection and iron supplement intake was associated with anaemia of pregnant mothers in Ambon City.